Market Oriented Agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Million Tadesse, Alaba, Ethiopia: 'Make the bulletin as a multidisciplinary one; mostly I found CTA focusing on theagronomic part of agricultural development. What about the socio-economic aspects?' Spore: This proposal fits very well with the...